2017
DOI: 10.1038/s41699-017-0021-7
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic etching of graphite and graphene in a remote hydrogen plasma

Abstract: We investigate the etching of a pure hydrogen plasma on graphite samples and graphene flakes on SiO2 and hexagonal Boron-Nitride (hBN) substrates. The pressure and distance dependence of the graphite exposure experiments reveals the existence of two distinct plasma regimes: the direct and the remote plasma regime. Graphite surfaces exposed directly to the hydrogen plasma exhibit numerous etch pits of various size and depth, indicating continuous defect creation throughout the etching process. In contrast, anis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 57 publications
9
25
1
Order By: Relevance
“…The anisotropically etched edges in our work are consistently armchair-oriented, in contrast to the zigzag-oriented edges or isotropic holes reported previously for oxidative graphene etching [19][20][21][22][23][24][25] and remote hydrogen plasma etching. 30,31 Vacuum annealing graphene at high temperatures in situ in the TEM has previously been reported to result in primarily armchair edges. 32,33 At lower pressures where we obtain more regular hexagons, the conditions are more similar to the high vacuum conditions of these reports, and carbon oxidation here might occur at a rate low enough to allow carbon atoms to re-arrange to form armchair edges.…”
Section: Resultsmentioning
confidence: 99%
“…The anisotropically etched edges in our work are consistently armchair-oriented, in contrast to the zigzag-oriented edges or isotropic holes reported previously for oxidative graphene etching [19][20][21][22][23][24][25] and remote hydrogen plasma etching. 30,31 Vacuum annealing graphene at high temperatures in situ in the TEM has previously been reported to result in primarily armchair edges. 32,33 At lower pressures where we obtain more regular hexagons, the conditions are more similar to the high vacuum conditions of these reports, and carbon oxidation here might occur at a rate low enough to allow carbon atoms to re-arrange to form armchair edges.…”
Section: Resultsmentioning
confidence: 99%
“…It is because the increase in graphene nucleus density with decreased H 2 content due to the hydrogen etching resulted in a smaller graphene grain size [ 44 ]. Thus, the possible lowering of the hydrogen plasma-induced defect density with decreased hydrogen gas flow should be considered [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are conflicts among previous experimental results on monolayer graphene exfoliated on SiO 2 . Yang et al [39] reported successful creation of hexagonal nanopits of uniform size, while Diankov et al [40] and Hug et al [41] reported circular ones. For a zGNR unzipped from a carbon nanotube, no nanopit creation by H-plasma etching has been found [32].…”
Section: Introductionmentioning
confidence: 99%